2004
DOI: 10.1097/01.asn.0000133698.80390.37
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hyperinsulinemia, Hypertension and Progressive Renal Disease

Abstract: Abstract. The incidence of end-stage renal disease (ESRD) has risen dramatically in the past decade, mainly due to the increasing prevalence of diabetes mellitus, and both impaired glucose tolerance and hypertension are important contributors to rising rates of ESRD. Obesity, especially the visceral type, is associated with peripheral resistance to insulin actions and hyperinsulinemia, which predisposes to development of diabetes. A common genetic predisposition to insulin resistance and hypertension and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 59 publications
6
137
1
3
Order By: Relevance
“…Clinically, it has been shown that insulin resistance and hypertension are major contributors of renal dysfunction (22). In line with the above study, in our animal model, invasive blood pressure measurement showed an increase in MAP and Ang II-induced ⌬MAP, which could not be reversed upon diet reversal.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Clinically, it has been shown that insulin resistance and hypertension are major contributors of renal dysfunction (22). In line with the above study, in our animal model, invasive blood pressure measurement showed an increase in MAP and Ang II-induced ⌬MAP, which could not be reversed upon diet reversal.…”
Section: Discussionsupporting
confidence: 73%
“…Metformin Improves Cardiovascular Function-It has been postulated that elevated basal MAP exacerbates nephropathy (22). To investigate this phenomenon, invasive blood pressure was measured in our study.…”
Section: High Fat Diet Feeding Induces Insulinmentioning
confidence: 99%
“…Despite progress in pharmacological strategies to control diabetes, hypertension and other metabolic abnormalities, the number of patients entering ESRD because of diabetic nephropathy remains extremely high, and the development of new classes of therapeutic reagents is eagerly anticipated [2]. During recent decades, the pathophysiology of diabetic nephropathy has become complex and serious because of coexisting lifestylerelated disorders, such as hyperlipidaemia, hypertension and obesity [3]. In fact, hyperlipidaemia is an independent risk factor for the progression of diabetic nephropathy in both type 1 and type 2 diabetes [4,5], but the underlying molecular mechanism remains elusive [6].…”
Section: Introductionmentioning
confidence: 99%
“…Microalbuminuria has been shown to be related to insulin resistance and hyperinsulinaemia [35][36][37][38][39], and other components of metabolic syndrome, including blood pressure [40,41], high levels of triglycerides and apolipoprotein B [42,43] and obesity [44]. When the 1998 WHO Consultation report [13] introduced microalbuminuria as a component of metabolic syndrome, this decision was evidently based on the association of microalbuminuria with insulin resistance and other components of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%